Applied diplomacy through the prism of mythology - "Sreenivasan, T.P." (New Delhi, 2014)
This book throw a light on a multiplicity of diplomatic issues that surfaced in the last decade in a manner, which only a seasoned diplomat, a deep thinker and a gifted writer could do.
Keywords: Hinduism